2011
DOI: 10.4102/sajip.v37i1.900
|View full text |Cite
|
Sign up to set email alerts
|

Positive organisation: The role of leader behaviour in work engagement and retention

Abstract: <strong>Orientation:</strong> The positive organisation creates a framework in which its elements can be investigated in relation to the retention of talent.<p><strong>Research purpose:</strong> The aim of this study was to investigate if leader empowering behaviour can positively impact on role clarity, psychological empowerment and work engagement, with the final outcome being the retention of talent.</p><p><strong>Motivation for the study:</strong> In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 53 publications
1
72
0
1
Order By: Relevance
“…Two studies found that leader empowering behaviour and engagement were linked. 178,187 Positive links were also found between authentic leadership and engagement, 239 while Wang and Hsieh 275 showed that this association was partially mediated by trust. Other aspects of leadership found to be positively associated with engagement were charismatic leadership 123 and supervisory coaching.…”
Section: Perceived Leadership and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies found that leader empowering behaviour and engagement were linked. 178,187 Positive links were also found between authentic leadership and engagement, 239 while Wang and Hsieh 275 showed that this association was partially mediated by trust. Other aspects of leadership found to be positively associated with engagement were charismatic leadership 123 and supervisory coaching.…”
Section: Perceived Leadership and Managementmentioning
confidence: 99%
“…233 May et al 22 found that the association between job enrichment and engagement was fully mediated by experienced meaningfulness. One study 178 found a link between meaning and engagement. Two further studies have looked at meaning-making or meaning in work; Heuvel et al 251 found that meaning-making was unrelated to engagement and Ghadi et al 248 found that meaning in work was correlated with engagement and that meaning in work partially mediated the link between transformational leadership and engagement.…”
Section: Individual Psychological Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reporting results on reasons why employees choose to leave or stay with a particular organisation (Bothma & Roodt, 2012;Du Plooy & Roodt, 2010;Greyling & Stanz, 2010;Griffeth, Hom & Gaertner, 2000;Kotzé & Roodt, 2005;Mendes & Stander, 2011) are gaining importance and most of them focus on a set of negative consequences associated with employee turnover (Bluedorn, 1982;Greyling & Stanz, 2010;Mobley, 1982;Roodt & Bothma, 1997). Corporate sustainability issues are gaining momentum and an example of this is the behaviour of the modern and informed investor who no longer assesses the quality of the organisation at present, but the organisation's risk management and whether it has established sustainability strategies pertinent to its business (King III Report, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Delegating authority, emphasising accountability, encouraging self-directed decision-making, developing skills and coaching to promote innovation (Konczak, Stelly, & Trusty, 2000) will promote the autonomy satisfaction of employees and will contribute to competence satisfaction. Mendes and Stander (2011) found that promoting role clarity (by reducing role ambiguity and conflict) could promote experiences of competence, which affect the retention of employees.…”
Section: Discussionmentioning
confidence: 99%